A Monte Carlo simulation for the improvement of drinking water and sewerage services in a northern settlement in Peru - Carhuanayocc Chancasanampa, Rossy (2022)
Clean water and sewerage systems are essential for global and local development. In Perú, even though most of its urban population has access to these services, it does not mean that those services are enough for the population's necessities. Moreover, they usually do not have acceptable quality. Consequently, it is necessary to invest public funds to provide clean water and sewerage systems to the possible people. However, it does not mean spending money carelessly on projects that might not fulfill people's demands. Then, the current research applied a Monte Carlo-based risk analysis for a public investment project seeking to improve those services in a poor human settlement on the northern coast of Peru. Hence, the Monte Carlo simulation was employed along with its sensitivity analysis. The research found that the project had an excellent chance of being sustainable. Still, it was necessary to make real improvements in the service to meet the population's needs, for instance, by improving the water quality or expanding the hours of clean water supply. Also, due to the investment's quantity, the project's sustainability depends on population growth and public expense efficiency. Finally, the importance of correctly maintaining the works to keep and improve those services was highlighted.